Strengthening of early children's character education stunting children in Indonesia - Adhar Arifuddin; Darmiyati Zuchdi; Dadan Rosana; Novita Intan Arovah; Caly Setiawan; Yuli Prihatni; Ari Setiawan; A Fahira Nur; Nur Eka Dyastuti; Hidayanti Arifuddin (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Forming human resources (HR) with character is challenged by social phenomena that show degradation of morality, ethics, and morals, as well as violent extremism. This is the basic reason for the importance of the strengthening character education (SCE) movement, which involves education units, families, and communities, and education must be implemented from early childhood, especially for children who are stunted. This study aimed to describe how the strategy for SCE is based on early childhood education classes for stunted children.MATERIALS AND METHODS: This type of research is qualitative research with a phenomenological approach. The participants in this study were the headmaster and teachers of Kindergarten PGRI Donggala Regency, Indonesia, in 2022. Collecting data using a questionnaire was equipped with interviews. The data were analyzed by content analysis, namely the process of identifying, coding, and categorizing important patterns from the results of in-depth interviews.RESULTS: The results of the study showed various patterns that became research themes as strategies for strengthening SCE in early childhood including integrating character values in learning for stunted children, introduction of SCE to stunted children, SCE habituation to stunted children, strengthening SCE for stunted children, and reflection on SCE for stunted children. Various character values produced in SCE include religiosity, creativity, curiosity, hard work, honesty, discipline, friendship, social care, independence, and responsibility.CONCLUSIONS: Each school for early childhood has a learning program that focuses on developing children's abilities in terms of motor, cognitive, social-emotional, language, and religious and moral values. However, schools must also have an adequate character education program, especially in dealing with children who are stunted, social-emotional, language, and religious and moral values.